Vanilla baosangii (Orchidaceae, Vanilloideae), a new species from the Central Highlands of southern Vietnam - Dang, Minh Quan; Averyanov, Leonid V.; Maisak, Tatiana V.; Tran, Thi Thuy Nhan; Nguyen, van Canh; Dang, van Son; Huynh, Huu Duc; Nguyen, Truong Giang; Truong, Quang Tam; Truong, Ba Vuong (Phytotaxa, 2025)
Vanilla baosangii discovered in the Central Highlands of southern Vietnam (Don Duong District, Lam Dong Province), is described and illustrated. In floral morphology the new species is similar to Vanilla siamensis and V. tiendatii in having hairs on the apex of the epichile and hairy column. However, it differs from V. siamensis in fewer, but densely arranged, flattened, often forked hairs on median lip lobe, a verruculose surface between the hairy epichle and bunch of scales, two warty keels forming a groove inside the claw, lip side-lobes surface with four to five distinct verruculose lines, lateral wings of clinandrium prominent, semi-circular, and anther cap ca. 4 mm long, with 2 forward curved horns. From V. tiendatii the new species differs in having larger elliptic leaves 18–26 cm long, an inflorescence bearing up to 25 flowers, lip apex with a group of fat branched hairs 4–7 mm long, and column with dense long hairs at apex, much longer than those in the basal half. According to IUCN Red List Categories and Criteria V. baosangii is assessed as a Critically Endangered. An identification key to all species to Vanilla known in Vietnam is provided, based on recent taxonomic treatments.